Characteristics of entropy generation and heat transfer in double-layered micro heat sinks with complex structure. (October 2015) - Zhai, Y.L.; Xia, G.D.; Liu, X.F.; Wang, J.
Highlights: A novel DL-MCHS with complex structure is presented. A model of entropy generation rate of DL-MCHSs is derived from the first and second laws of thermodynamics. DL-MCHSs show better thermodynamic advantage and thermal performance under large volumetric flow rate. Abstract: A new type of double-layered micro heat sink (DL-MCHS) with complex structure is designed and investigated numerically. Moreover, a model of entropy generation rate of DL-MCHSs is also derived from the first and second laws of thermodynamics. Results for the relationship of entropy generation rate between the first and second layer of DL-MCHSs, total entropy generation rate, the average temperature on the bottom wall, thermal resistance and pressure drop are investigated in detail, respectively. The results indicate that the effect of entropy generation rate of the first layer on total entropy generation rate is dominant. The thermal characteristic of DL-MCHSs with complex structure is better than that of all DL-MCHSs and single-layered micro heat sinks (SL-MCHSs) with simple structure under the same volumetric flow rate. However, DL-MCHSs only show better thermodynamic advantage and thermal performance than SL-MCHSs with complex structure when the volumetric flow rate larger than a certain value. It is not reasonable to use DL-MCHSs for cooling microelectronic equipments under small volumetric flow rate due to the larger irreversibility. Finally, the pressure drop of DL-MHCSs can be reduced by properly changing the channel height under various volumetric flow rates. Due to the less irreversibility and more uniform temperature distribution on the bottom wall, DL-MCHSs can effectively eliminate the internal thermal stresses in microelectronic equipments. Therefore, DL-MCHSs are an alternative method for the electronic cooling. Moreover, the thermodynamic analysis provides references for the actual application design.